Trabalhadores do "lixo": a organização das cooperativas de catadores de materiais recicláveis em São Paulo 2000/2005 - Scarpinatti, Mauro (2008)
This research sought register the experience of deploying cooperatives of collectors recyclable materials in the city of São Paulo, between the years 2000 and 2005. The recycling of waste is a very current subject, especially considering the emergence of global concerns with the emissions of pollutants, in clear contradiction with the capitalist society whose basic logic is the increasing elevation of consumption to ensure the reproduction of capital. Historically in we accustom them to label the remains simply as "garbage". In this generic name, attach meanings as dirty, bad smell, infected. By extension, "the garbage workers" are often contaminated as if they were carrying the same meanings assigned to "garbage", and so become stigmatized. The research proposed to deal with the issue from the point of view of social organization in this way, the clipping of this work is the organization of workers in cooperatives of Collectors Materials Recyclables. That is, describe the process as organized the residents of the street, unemployed and all survivors of an economic model exclusionary and perverse from the debris discarded by the city to create means of survival, generate jobs and income and form a movement Social able to make them visible socially and in fact constituted them in new social subjects, which in a short space of time have achieved national presence. The first chapter, searchs to locate the collector historically, the first steps towards collective action, organizations of support, the collisions with the city hall and the creation of the first cooperative. The second chapter deals with the unemployeds who becomes collectors, the disputes around "garbage" and extension of the joints to a movement nationwide. In the third and final chapter is presented the municipal program Solidarity Selective Collection, that between the years 2000/2004, implemented 15 officces Central Screening of waste , run by cooperatives of collectors, in the city of Sao Paulo